Rethinking the ‘Arab Spring’: the root causes of the Tunisian Jasmine revolution and Egyptian January 25 revolution - Mohd Irwan Syazli Saidin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article reviews the events of 2010-2011 Tunisian and Egyptian revolutions with specific attention to the background of uprisings, timeline of events and causes of the revolutions. The focus of this study is to look into the factors that ignited the revolutions, both in Tunisia and Egypt. By examining secondary sources mainly through published reports dan journal articles, it will highlight how the uprisings in Tunisia and Egypt evolved besides shedding light on the 2011 Arab Spring event. A number of factors have been selected under five main themes namely economics development, political legitimacy, social demography, Islamism and the advance of new social media. All these factors, to large extent have contributed to the causes of this popular uprisings which led to the collapse of the previous regime of Ben Ali and Hosni Mubarak. Among these factors, the role of new social media was identified as the main factor which secure the successful of the revolutions in Tunisia and Egypt and considered as a new platform of political protest in the Middle East and North Africa.